Why English Literature Students in Indonesia Refuse to Become Writers - Rahmat Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines how English literature students in Indonesia refuse to become writers. This study employed a mixed-methods design combining quantitative surveys and qualitative interviews. With an explanatory sequential approach, data were collected from 100 English literature undergraduates across five universities through a 15-item Likert questionnaire analysed with SPSS 26 (Kolmogorov-Smirnov, Mann–Whitney, and Kruskal–Wallis tests). Three representative students (X, Y, Z) were interviewed using semi-structured questions, and data were thematically analysed. Results from survey and interviews reveal that literature students hold positive opinions of their studies but elaborate little interest in becoming writers. They choose the major mainly for language skills, not creative goals. The curriculum supports academics, not authorship, and financial instability deters writing careers, unaffected by gender or semester differences. The study concludes that English literature in Indonesia faces a paradigmatic tension between academic formalism and artistic vitality. To address this, it requires redirection that integrates creative writing, publication mentorship, and intermedial collaboration to reinstate productivity in literary works.